Wpływ literatury polskiej na świadomość społeczeństwa bułgarskiego (nadzieje tłumacza) - Spasowa, Prawda (Postscriptum Polonistyczne, 2020)
The author expresses her hopes that translations and promotion of Polish literature will initiate certain turn to openness and dialogue within Bulgarian community. It was lost during the period of the socalled ‘real socialism’.